Homologous Over-Expression of Chain Length Determination Protein EpsC Increases the Molecular Weight of Exopolysaccharide in Streptococcus thermophilus 05-34 - Zhai, Zhengyuan; Xie, Shuxin; Zhang, Hongxing; Yi, Huaxi; Hao, Yanling (Frontiers in Microbiology, 2021)
In S. thermophilus, EpsC is a polysaccharide co-polymerase which is involved in determining the chain length of EPS synthesized by the Wzx/Wzy-dependent pathway. Our previous study found that there was a positive correlation between transcription level of epsC and molecular weight of EPS in S. thermophilus 05-34. To further investigate the effects of EpsC on EPS biosynthesis, this gene was over-expressed in S. thermophilus 05-34 in this study. Reverse transcription qPCR and Western blotting confirmed the successful transcription and translation of epsC in 05-34, respectively. The yield of EPS was not affected by the overexpression of EpsC. Gas chromatography-mass spectrometry (GC-MS) showed that the monosaccharide composition was still composed of galactose and glucose in a molar ratio of 1.0:0.8, whereas high performance gel permeation chromatography indicated that the molecular weight of EPS was increased from 4.62×105 Da to 9.17×105 Da by the overexpression of EpsC. In addition, S. thermophilus 05epsC which could produce higher molecular weight EPS improved the viscoelasticity and water-holding capacity of yoghurt, but significantly reduced the level of syneresis in yoghurt. In summary, these results indicated that homologous overexpression of EpsC in S. thermophilus could increase the molecular weight of EPS and improve the microrheological or physical properties of yoghurt.